Specific Proposals for Innovation Teaching and Its Impact on Future Challenges for Basic Level Pupils (Asian Education Studies, 2016)
This paper primarily aims at exploring the impact of innovation teaching on future challenges for basic level pupils. The descriptive analytical and experimental methods are used in this research. The researcher can put specific proposals for innovation teaching for basic level pupils. The study sample consists of pupils totaling (20) pupils of the basic schools of the University of Khartoum - Republic of the Sudan. Innovation and creativity are part of the essential skills that enable students to meet with future challenges, can implement a number of tips and techniques that can help students to think creatively and find solutions for future problems. The results showed there are significant differences between the experimental group and control group before and after the test, which confirms that students of the basic schools will be more interested in the future challenges as measured by a survey given before and after the program. The researcher recommended the Ministry of Education should develop a plan focusing on the development of the children creative abilities of the basic level pupils, because student at this level tends to invent things or find solutions.